Desain Kendali Kecepatan Motor DC Pada Mobile Robot Mecanum Wheels - Imam Taufiqurrahman; Andri ulus Rahayu; Moch Yuagga Permana; Ramdani R (E-JOINT (Electronica and Electrical Journal Of Innovation Technology), 2024)
In an era of rapid technological development, the challenges facing the industrial sector in terms of automation continue to increase. Robotics is now present as one of the solutions and continues to be the focus of various studies. Mobile robots, with different numbers and types of wheels, are one of the types that are being widely researched to meet automation needs. One innovation that is attracting attention is the use of mecanum wheels, which provide omnidirectional motion capabilities that are far superior to conventional wheels. This research develops a control system for the DC motor used in the mecanum wheel mobile robot. This control design aims to provide precision in controlling the speed and direction of the robot's motion. By applying the PID (Proportional-Integral-Derivative) control technique, the system is able to optimally regulate the speed of each DC motor on all four wheels, allowing the robot to move smoothly in all directions. This research produces a PID controlled DC motor with a rise time of less than 15 seconds and PID parameters of Kp = 10, Ki = 0.5 and Kd = 2. The generated parameters can be used to control the speed of DC motors on mobile robots with mecanum wheels.